Product offerings testing through customer satisfaction - Vukasovič, Tina (Management, 2014)
Consumer satisfaction is imperative to a successful business, the reason for the choice of topic for this paper being explained thereby. Market changes have resulted in consumer's enormous growth of power, which was recognized by many companies who adapted their business to meeting those expectations. Adaptation, however, also resulted in the need for constant measuring and evaluation. According to the above-mentioned, this paper measures consumer satisfaction with the product offer of the drugstore chain X The survey results have shown that X's offer has not completely come up to the expectations of a smaller number of interviewees. In relation to the measuring ranks of consumer satisfaction defined, the greatest number of consumers has turned out to be satisfied with the product offer, whereas the percentage of those who find it excellent is smaller than the percentage of those who assess it as average.
Keywords: kupci; merjenje; ponudba; potrošniki; zadovoljstvo